Market development programme for non-traditional agricultural products from countries of CARICOM : final report (David Jones and Associates TeddingtonGB, 1988)
Discusses horticultural production in the CARICOM region and reviews agronomic resources, farm types, important crops and the post-harvest handling system. Identifies production opportunities, problems and constraints. Provides overview of existing intra- and extra-regional trade in non-traditional fruit,vegetables and floricultural products. Presents island by island data on the level of trade and role of participants. Examines work done by the Caribbean Agricultural Trading Co. Reviews trends in the markets of the UK, Europe and The USA for tropical fruits and vegetables. Recommends ways of dealing with constraints to marketing of above products. Designs 5 year programme to develop regional exports of non-traditional products.
Keywords: AGRICULTURAL PRODUCTION